Transmission Power Control in Multi-Hop Communications of THz Communication Using a Potential Game Approach - Evangelos D. Spyrou; Vassilios Kappatos; Chrysostomos Stylios (Future Internet)
Terahertz (THz)-band communications are a possible candidate for fast communication. Transmission power needs to be optimised in order to satisfy the requirements of such a network of nodes. Multi-hop communication can be used in THz communications to add relays when obstacles or other interference is evident. This paper investigates the domain of multi-hop THz communications, acknowledging the possibility of interference from other devices affecting the communication process and utilises interference cancellation. It formulates the Transmission Power Control (TPC) problem within a game-theoretic framework, specifically as a potential game, with the assurance of convergence to a Nash equilibrium in the majority of scenarios. Bounds of the Price of Anarchy (PoA) and the Price of Stability (PoS) are provided, given assumed factors. Also, asymptotic Lyapunov stability is shown. The findings from simulations conducted to assess the effectiveness of this approach are then discussed. In particular, the final utilities when utilising interference cancellation show an improvement compared to without-interference cancellation between 19.30 and 67.30% for five simulated players.